Dual chaotic encryption method for wireless communication privacy data based on deep learning - Hongbo Yu (PLoS ONE, 2026)
In wireless communication, the multipath effect and the time-varying channel due to mobility will directly lead to the key update cycle lagging far behind the channel change, which is difficult to effectively resist various malicious attacks and stealing behaviors, and affects the effect of privacy data protection in wireless communication. To this end, a deep learning-based dual chaos encryption method is proposed for wireless communication privacy data. Combining the chaotic characteristics of one-dimensional Logistic mapping and two-dimensional Henon mapping, the dual chaotic key is generated to extend the key space and improve the anti-attack ability; and the bidirectional long and short-term memory network (BiLSTM) is used to analyze the data such as key usage records, accurately predict the timing of the key updating, and generate a new key when anomalies are detected, and then distribute it securely. Taking the updated double chaotic key as input, the AES algorithm is used to realize wireless communication privacy data encryption through key expansion, initial round encryption, multiple rounds of iterative encryption and final round encryption, while the decryption process restores the plaintext by inverse operation. Experiments demonstrate that the method can effectively realize wireless communication privacy data encryption, and the security index can reach more than 0.94 in the face of different types of network attacks. It demonstrates that the proposed method can have the ability to resist all kinds of attacks and protect the security of private data.